The last days of Kim Jong-il : the North Korean threat in a changing era - Bechtol, Bruce E., 1959- (Potomac Books, 2013)
North Korea has remained a thorn in the side of the United States ever since its creation in the aftermath of the Korean conflict of 1950 - 1953. Crafting a foreign policy that effectively deals with North Korea, while still ensuring stability and security on the Korean Peninsula - and in Northeast Asia as a whole - has proved very challenging for successive American administrations. In the wake of ruler Kim Jong-il's death in December 2011, analysts and policymakers continue to speculate about the effect his last years as leader will have on the future of North Korea. Bruce Bechtol, Jr. conte.